EVALUASI PRINSIP GOOD ENVIRONMENTAL GOVERNANCE (GEG) DALAM PENERAPAN KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN KENDAL - Anam Hady Nugroho; Budi Setiyono; Sulistyowati . (Journal of Politic and Government Studies, 2015)
The increasing of society’s consumption as the result of the economic growth and the increasing of population lead to the increasing of waste problems in Kendal. Whereas, the waste management’s capability in Kendal is less effective to create a good environmental governance into the regulation of waste management.The aim of this research is (1) to know what kinds of the good environmental governance’s principle which can be found in Kendal’s Regional Regulation No. 13 years of 2012 about waste management and to know how this principle is implemented. (2) To understand the problems which are faced by the government through the implementation of this principle.This research is the evaluative research with the qualitative approach. The methods of collecting data in this research use interview, observation, and documentation. The data’s analysis uses the descriptive analysis to describe the situation in the research obviously without any manipulation.There are six principles of good environmental governance which can be found in this research. Those principles are integrated in the regional regulation about waste management as follows: the empowerment, the involvement of society and publics access toward information; transparency; decentralization and democracy; the confession of the indigenous people and the local society; recognition of the sustainability and the carrying capacity of ecosystems; and rule of law. Some of the principle above can be implemented well, while some of them cannot be implemented. The problems which had to face come as follows: the poor communication among government board; the uneven communication toward society; the low public awareness; the unexperienced-human resources in waste management (management, innovation, initiative); the lack of waste management infrastructure; the limited budget for waste management; the lack of management’s commitment; the constringency of waste management.Keyword: Good Environmental Governance, Waste Management.